Prediction of vulnerability to bipolar disorder using multivariate neurocognitive patterns: a pilot study - Mon-Ju Wu; Benson Mwangi; Ives Cavalcante Passos; Isabelle E. Bauer; Bo Cao; Thomas W. Frazier; Giovana B. Zunta-Soares; Jair C. Soares (International Journal of Bipolar Disorders, 2017)
Abstract Bipolar disorder (BD) is a common disorder with high reoccurrence rate in general population. It is critical to have objective biomarkers to identify BD patients at an individual level. Neurocognitive signatures including affective Go/No-go task and Cambridge Gambling task showed the potential to distinguish BD patients from health controls as well as identify individual siblings of BD patients. Moreover, these neurocognitive signatures showed the ability to be replicated at two independent cohorts which indicates the possibility for generalization. Future studies will examine the possibility of combining neurocognitive data with other biological data to develop more accurate signatures.